Homelands : shifting borders and territorial disputes - Shelef, Nadav G. (Nadav Gershon), 1974- (Cornell University Press, 2020)
"Nadav G. Shelef explains that homelands matter deeply in domestic and international politics, their contours can change, and domestic political competition drives those changes"--